2021
DOI: 10.1002/cncr.33385
|View full text |Cite
|
Sign up to set email alerts
|

Olmutinib in T790M‐positive non–small cell lung cancer after failure of first‐line epidermal growth factor receptor‐tyrosine kinase inhibitor therapy: A global, phase 2 study

Abstract: Background In this open‐label, international phase 2 study, the authors assessed the efficacy and safety of olmutinib in patients with locally advanced or metastatic non–small cell lung cancer (NSCLC) who had a confirmed T790M mutation and disease progression on previous epidermal growth factor receptor‐tyrosine kinase inhibitor therapy. Methods Patients aged ≥20 years received once‐daily oral olmutinib 800 mg continuously in 21‐day cycles. The primary endpoint was the objective response rate (patients who had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 37 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…The efficacy of olmutinib against cell lines harboring the T790M mutation has been demonstrated in preclinical studies. The results of clinical trials demonstrated that olmutinib exhibited significant efficacy in patients diagnosed with T790M-positive NSCLC who experienced disease progression following prior TKI therapy, thereby providing a novel treatment option [62]. However, the clinical development of the drug faced challenges due to reports of serious adverse events such as severe skin toxicity and the rare but serious side effect known as Stevens-Johnson syndrome [63].…”
Section: Olmutinibmentioning
confidence: 99%
“…The efficacy of olmutinib against cell lines harboring the T790M mutation has been demonstrated in preclinical studies. The results of clinical trials demonstrated that olmutinib exhibited significant efficacy in patients diagnosed with T790M-positive NSCLC who experienced disease progression following prior TKI therapy, thereby providing a novel treatment option [62]. However, the clinical development of the drug faced challenges due to reports of serious adverse events such as severe skin toxicity and the rare but serious side effect known as Stevens-Johnson syndrome [63].…”
Section: Olmutinibmentioning
confidence: 99%
“…On the other hand, the first-line naquotinib resulted in an ORR of 52%, DCR of 94%, and PFS of 11.3 months. However, the phase 3 clinical trial of naquotinib was closed due to limited predicted efficacy and toxicity [ 177 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In January 2021, the Korean Food and Drug Administration (MFDS) approved the listing of lazertinib for the treatment of patients with locally advanced or metastatic NSCLC positive for EGFR T790M mutations who previously received EGFR-TKI treatment (36). The third-generation EGFR-TKIs olmutinib (37)(38)(39) and nazartinib (40) are also approved in South Korea.…”
Section: Changes In Egfr T790m Mutationmentioning
confidence: 99%